Evolution of human needs in changing civilizations - Bardis, Panos D. (The Greek Review of Social Research, 1974)
The theory presented in this study is that, as science and technology advance and the resulting affluence generates higher levels of satisfaction for man’s physiological drives, our emphasis on sociopsychological needs becomes greater and greater. The data employed to test this theory were of two types: one, macroanalytical or historical, and two, microanalytical or semihistorical, the latter being the problems and needs of New York’s «neediest» families. At least the data included here do support the theory. The numerous implications of these findings are obvious. Below are a few of them: 1. We need a standardized and more precise and systematic nomenclature of human needs in order to study them more fruitfully. 2. Our increasing affluence necessitates further research into the psychology and sociology of leisure time. 3. More meaningful education in this sector is also necessary. 4. We must explore the exact relationship between frustration and violence. 5. Social planning in these areas is something that can no longer be postponed with impunity. 6. The developing economies of the Third World will generate new sociopsychological needs which, unless appropriate measures are taken, may result in social unrest and even violence. 7. Finally, the utopian plans of those who conceive of purely economic solutions as sufficient panaceas are simplistic and ludicrous, as they reveal their advocates’ inability to understand the nature of both our physiological and sociopsychological needs. Unfortunately, although physical satiety is often easy to achieve, there is no answer, for instance, to this question: When does a man have enough power? For man’s sociopsychological needs are insatiable, boundless, unfathomable!